Chemistry Go to School: Meningkatkan Minat Belajar Kimia Siswa SMA di Kotamobagu dan Bolaang Mongondow Melalui Sosialisasi dan Demo Fun Chemistry - Sufriyanto Ibrahim; Haris Munandar; Djafar La. Kilo; Ahmad Kadir Kilo (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2025)
This study aims to increase students' interest and understanding of chemistry through socialization and improvement of Fun Chemistry. The methods used include delivering material about the field of Chemistry and job prospects, as well as simple chemical experiments such as Secret Messages and Elephant Toothpaste. The results of the study showed that this activity succeeded in increasing students' interest in Chemistry, with most students considering continuing their studies in the Chemistry department. The evaluation showed a positive impact on students' motivation and interest in entering and studying in the Chemistry department..